2018
DOI: 10.28945/4129
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Educational Technology Confidence among Teacher Candidates: Benefits of and Lessons Learned from a 1:1 Device University-Elementary School Partnership

Abstract: Aim/Purpose: This study describes and evaluates a teacher preparation program that combines a school-university partnership and a 1:1 device initiative. Background: This educational design research report combines a 1:1 technology device experience with a school-university partnership to enhance teacher preparation for educational technology use. Methodology: This is a mixed-methods educational design research study. Interview responses share benefits and lessons learned from the program experience. Surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…It is necessary to attract university students as curators and project mentors in order to support practical part of the project implementation of schoolchildren. Students can be involved in project activities when they obtain competencies in the organization of project activities [11,15,16].…”
Section: Methodsmentioning
confidence: 99%
“…It is necessary to attract university students as curators and project mentors in order to support practical part of the project implementation of schoolchildren. Students can be involved in project activities when they obtain competencies in the organization of project activities [11,15,16].…”
Section: Methodsmentioning
confidence: 99%
“…With the increasing integration of technology in K-12 classrooms, this change makes it necessary for teachers to have a deep understanding and efficiency in technological tools to be able to train individuals with the skills required for using the 21 st century technological tools (Giles, 2019). Thus, it was observed that teacher education programs aim to train pre-service teachers with the necessary skills to integrate technology into teaching and learning experiences (Francom and Moon, 2018). The presence of pre-service teachers with these skills will lead to future good practices (Giles, 2019).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Cabaleiro-Cerviño and Vera (2020) highlighted the crucial significance of educational technology in facilitating profound transformations within the classroom. As a result, teacher preparation programmes in universities have the goal of providing teacher candidates with the necessary abilities to effectively incorporate technology into their teaching and learning experiences (Francom & Moon, 2018). Tolulope et al (2015) emphasised the profound influence of technology in higher education, fundamentally changing the way teaching and learning are conducted.…”
Section: Literature Reviewmentioning
confidence: 99%